A vaccine for photodynamic immunogenic cell death: tumor cell caged by cellular disulfide–thiol exchange for immunotherapy. (10th December 2020) - Wen, Ya; Liu, Yiqiong; Guo, Fangfang; Han, Yi; Qiu, Qiansai; Li, Yan; Dong, Haiqing; Ren, Tianbin; Li, Yongyong
Abstract : Tumor cells, caged by the protein shell, are mediated to an immunogenic cell death and transformed into a hot cell vaccine. Such vaccine protects 75% pre-immunized mice against tumor initiation and significantly retards the established tumor growth. Abstract : It has been suggested that immunogenic cell death (ICD) has therapeutic potential; however, its anticancer immunity is considerably hampered by the in situ immunosuppressive microenvironment within the tumor area, such as the dysfunction of antigen-presenting cells. Herein, we present an in vitro ICD-inducing modality to circumvent such impairment of immune activation. To this end, a "hot", i.e., immunogenic, whole tumor cell vaccine is generated in vitro and subcutaneously vaccinated in the normal tissue, departing from the site of the in situ immunosuppressive tumor area, to fully leverage the ICD-inducing antitumor immunity. In particular, the immunogenic dying tumor cells, caged by cellular disulfide–thiol exchange, are mediated by photoactivation. After subcutaneous vaccination, the photoactivated caged live cell vaccine (CLCV) exerts multi-durable immunostimulatory property, which, when adjuvanted by CpG, efficiently promotes dendritic cell (DC) activation and elicits robust CD8 + T-cell responses in vivo . Importantly, the generated T-cell responses are shown to protect 75% mice preimmunized with CLCV against tumor initiation and significantly retards tumor growth in the therapeutic setting. The strategy presented here may help to enrich the current vaccine design for cancer immunotherapy.